Relationship between intake of artificial sweeteners and body mass index in young non-diabetic adults: a cross-sectional study - Gupta, Geetika; Yograj, Sabita; Gupta, Anil K.; Langer, Bhavna; Goni, Mumtaz; Kalsotra, Lila (International Journal of Research in Medical Sciences, 2017)
Background: Artificial sweeteners have skyrocketed the market in the last decade and there are unlimited products available today that contain them. They are often projected as one of the easy and effortless method of cutting down calories and have gained importance in the community. They are being used as one of the dietary tools to control or prevent weight gain not only in diabetic adults but also in young healthy adults and children. There is a need to examine any possible contribution of these substances on body weight and BMI of an individual. Methods: A cross sectional study was conducted among randomly selected healthy non-diabetic subjects of both sexes in the age group 18-35 years. Those with history of intake of artificial sweeteners in the last one year (in the form of pellets or diet soda) were considered as study group and equal no of non-users were taken as comparison group for study purpose. A pretested semi structured questionnaire prepared in English language was used to collect information. Variables such as height, weight and body mass index were noted. Data was analyzed using SPSS (version 20.0). Results: There was a statistically significant difference between the two groups in terms of weight and BMI (p=0.003 and 0.002 respectively). The mean weight and BMI was more in those subjects who had consumed more than one serving of diet can per day. Sweeteners in pellet form failed to show any statistical significance association between frequency of use and BMI. Conclusions: The study suggested of a possible association between the use of artificial sweeteners and BMI. Young adults need to be sensitized about various safe weight management techniques and healthy lifestyle, rather than resorting to methods like intake of artificial sweeteners.